Advertising and integrated brand promotion - O'Guinn, Thomas; Allen, Chris T.;Semenik, Richard J. (Andover, Mass. : Cengage Learning Asia Pte Ltd, 2012)
It acknowledges the complexity of human communication and consumer behavior.
1. The world of advertising and integrated brand promotion -- 2. The structure of the advertising and promotion Industry: Advertisers , Agencies, Media and Support Organizations -- 3. The history of advertising and brand promotion -- 4. Social, Ethical and regulatory aspects of advertising and promotion -- 5. Advertising, Integrated brand promotion and consumer behavior -- 6. Market Segmentation, positioning and the value proposition -- 7. Advertising and promotion research -- 8. Planning advertising and Integrated brand promotion -- 9. Managing Creativity in advertising and IBP -- 10. Creative Message Strategy -- 11. Executive creative -- 12. Media Planning essentials -- 13. Media Planning: Newspapers, magazines, television and radio -- 14. Media Planning: advertising and IBP in Digital/ Interactive Media -- 15. Sales promotion, point of purchase Advertising and Support Media -- 16. Event sponsorship, product placements and branded entertainment -- 17. Integrating Direct marketing and personal selling -- 18. Public relations, Influencer marketing and corporate advertising.
Includes index.
Keywords: ADVERSTISING -- MEDIA PLANNING